Longitudinal uptake of the human papillomavirus vaccine among gay, bisexual and other men who have sex with men in British Columbia, Canada 2012–2019. (16th August 2021) - Khatra, Jatinder; Sang, Jordan Mitchell; Wang, Clara; Bacani, Nicanor; Lachowsky, Nathan John; Grennan, Troy; Burchell, Ann Natalie; Lal, Allan; Roth, Eric; Hogg, Robert; Card, Kiffer; Moore, David
Abstract : Objectives: In 2015, a publicly funded human papillomavirus (HPV) vaccination programme was implemented for gay, bisexual and other men who have sex with men (gbMSM) up to age 26 years in British Columbia, Canada. We assessed trends and correlates of HPV vaccine uptake from 2012 to 2019 in a cohort of gbMSM in Vancouver. Methods: We recruited sexually active gbMSM aged ≥16 years using respondent-driven sampling from February 2012 to February 2015 and followed them until July 2019. We evaluated self-reported HPV vaccine trends using mixed-effects logistic regression and identified factors associated with uptake using multivariable mixed-effects Poisson regression. Results: A total of 719 participants were recruited and completed the baseline visit, of whom 549 were unvaccinated with at least one follow-up visit. The median age was 33 years and 23% were living with HIV. HPV vaccination increased from 4% in 2012 to 28% in 2019 (p<0.001) among gbMSM >26 years, and from 9% in 2012 to 20% in 2017 (p<0.001) among gbMSM ≤26 years. Vaccination uptake increased after September 2015, following vaccination policy expansion (adjusted rate ratio (aRR)=1.82, 95% CI 1.06 to 3.12). In multivariable models, increased vaccination was associated with age ≤26 years vs ≥45 years (aRR=3.90; 95% CI 1.75 to 8.70), age 27–44 vs ≥45 years (aRR=2.86; 95% CI 1.46 to 5.62), involvement in gay community sports teams (aRR=2.31; 95% CI 1.15 to 4.64) and other groups (aRR=1.71; 95% CI 1.04 to 2.79), awareness of HIV-postexposure prophylaxis (aRR=5.50; 95% CI 1.31 to 23.09), recent sexually transmitted infection testing (aRR=2.72; 95% CI 1.60 to 4.60) and recent sex-work (aRR=2.59; 95% CI 1.08 to 6.19). Conclusions: Although we observed increases in HPV vaccination uptake from 2012, by 2019 HPV vaccination still remained below 30% among gbMSM in Vancouver, BC. Additional interventions are needed to increase vaccine uptake.